Resolução de problemas algébricos: uma investigação sobre estratégias utilizadas por alunos do 8º e 9º ano do ensino fundamental da rede municipal de Aracaju/SE - Silva, Mirleide Andrade (2015)
In this work, is presented the result of a research that had as main theme strategies used by the students of 8th and 9th for solving algebraic problems of the Municipal Aracaju / SE school. In another way, the objective of the research was identify and examine the strategies used by these students in solving algebraic problems. To achieve this purpose, students from schools in different geographic regions of Aracaju / SE were selected initially to respond a selection of mathematical problems taken from the textbook The Conquest of Mathematics by Geovanni and Castrucci Jr (2009). After an examination with one hundred eighty-two instruments, were conducted semi structured with twenty percent of the students. The main theoretical support was clamped in the work of George Polya (1978) entitled The Art of Problem Solving for the understanding of mathematical, algebraic, problem type and problem solving strategies. The author defends as the algebraic problem those which use them to solve algebraic content. In according of the statement of mathematical problems, Polya (1978) classifies as routine, practical and enigma, and the solution in determination and demonstration. It possible says that most students use arithmetic strategies in solving algebraic problems, because in routine problems, students didn t need to make a plan, only to solve questions. Moreover, in relation to the practical problems students needed to understand the problem and develop a solution strategy, they were compelled to understand the problems to formulate a plan, most showed doubts of statements and appealed to arithmetic strategies.